2011
DOI: 10.1186/1758-3284-3-27
|View full text |Cite
|
Sign up to set email alerts
|

The Hannover experience: Surgical treatment of tongue cancer - A clinical retrospective evaluation over a 30 years period

Abstract: ObjectivesIn this retrospective study, we present a clinical review of our experience with tongue cancer in order to obtain valid criteria for therapeutic decision-making.Materials and methodsBetween 1980 and 2009, a total of 341 patients with squamous cell carcinoma of the tongue were treated at our Department. The average follow-up was 5.2 years. 309 patients received surgical treatment, which was combined in nearly 10% with neoadjuvant and in nearly 20% with postoperative radio(chemo)therapy. 32 patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 43 publications
3
33
0
1
Order By: Relevance
“…Outcome results and comparison with the non-IMRT literature of patients treated for recurrent OCC after initial surgery only are shown in Table 4[8-11]. …”
Section: Resultsmentioning
confidence: 99%
“…Outcome results and comparison with the non-IMRT literature of patients treated for recurrent OCC after initial surgery only are shown in Table 4[8-11]. …”
Section: Resultsmentioning
confidence: 99%
“…A study in Hannover found that there is an increase of fiveyear survival which is 54.5% on patients who received surgery, compared to 13.7% without the surgery. This is possibly caused by 83.5% patients had tumor size T1 and T2 (Kokemueller et al, 2011). At DNCH, surgery therapy was done to 45.6% patients because more than half of the patients were already in stage 3 and 4 that were non-operable.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the tremendous improvements in surgery, radiotherapy and chemotherapy over the last decade, the prognosis for patients with tongue squamous cell carcinoma (TSCC) has remained relatively unchanged for the past 3 decades[1]. This is because patients continue to succumb to metastatic disease at regional and distant sites.…”
Section: Introductionmentioning
confidence: 99%